Business Strategic Analysis at PT Waterindex Tirta Lestari - Ni Luh Gita Priti Sari; Ayi Ahadiat (Asian Journal of Applied Business and Management, 2023)
This study navigates the turbulent waters of the AMDK industry, focusing on the Grand brand. The research unveils internal strengths like diverse packaging and robust quality control by utilizing strategic analyses such as IFE, EFE, SWOT, IE matrix, and QSPM. According to the result, stagnant market share poses an internal challenge. External opportunities emerge through potential collaborations with modern markets and the Radisson Lampung Hotel, while the looming threat of numerous refill depots adds complexity. The QSPM results advocate an intensive strategy, emphasizing market penetration by fortifying product quality, enhancing consumer services, and introducing compelling promotions. This study propels PT Waterindex Tirta Lestari to set sail with a dynamic strategy, ensuring a refreshing victory in the competitive sea of bottled water